NURSERY OF WHITE SHRIMP (LITOPENAEUS VANNAMEI) WITH BIOFLOC SYSTEM - witoko, pindo; Mahmudah Noor, Nuning; Aziz, Rahmadi (Program Studi Budidaya Perairan Universitas Mataram, 2023)
White shrimp culture (Litopenaeus vannamei) has very good prospects to be developed so that the availability of quality juveniles with a sustainable quantity is very necessary for aquaculture activities. White shrimp nursery has several constraints because in the implementation process it uses high stocking density so the amount of feed needed is higher. The condition of using high feed can have an impact on the quality of aquaculture used. Waste products from metabolism and uneaten feed residues, especially nitrogen waste can be toxic to shrimp. To reduce the risk of toxic waste in shrimp there are several technologies that can be used, one of which is biofloc technology. This study aims to determine the growth and survival rate (SR) of white shrimp nursery using biofloc technology. The study was conducted using a permanent ponds container coated with a tarpaulin with a size of 3m x 5m x 1.2m as much as 2 pieces. Each pond filled with seawater with a salinity of 30 ppt as much as 12,000 liters is equipped with 24 aeration points and a microbubble. White shrimp juvenile used Post Larva size 10 with an average weight of 0.01 grams with a stocking density of 1,500 ind/m3(18,000 ind/pond). Maintenance time for 28 days. During maintenance, commercial feed is given at a dose of 100% -5% of the total weight of biomass per day. The results showed an average final length and weight are 5.15 cm and 2.32 gram/ind with a Survival rate (SR) of 89.7%.